Share Your Knowledge (S.Y.O.K) - Sarah, Zulkiple (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
Share Your Knowledge (S.Y.O.K) was the second program of English Language Camp series conducted by Intelligentsia Club, UMP in collaboration with Maktab Rendah Sains Mara (MRSM), Kuantan.